2014
DOI: 10.1111/imm.12306
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium indicus pranii and Mycobacterium bovis BCG lead to differential macrophage activation in Toll‐like receptor‐dependent manner

Abstract: SummaryMycobacterium indicus pranii (MIP) is an atypical mycobacterial species possessing strong immunomodulatory properties. It is a potent vaccine candidate against tuberculosis, promotes Th1 immune response and protects mice from tumours. In previous studies, we demonstrated higher protective efficacy of MIP against experimental tuberculosis as compared with bacillus Calmette-Gu erin (BCG). Since macrophages play an important role in the pathology of mycobacterial diseases and cancer, in the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…An increase in IFN-γ and IL-2 cytokines and absence of IL-4 in the stimulated T cells (25) and production of high levels of TNF-α (46) have been reported with Mw adjuvant alone in mice. We did observe a correlation of gene and protein expression with Th1 and not Th2 cytokines.…”
Section: Discussionmentioning
confidence: 95%
“…An increase in IFN-γ and IL-2 cytokines and absence of IL-4 in the stimulated T cells (25) and production of high levels of TNF-α (46) have been reported with Mw adjuvant alone in mice. We did observe a correlation of gene and protein expression with Th1 and not Th2 cytokines.…”
Section: Discussionmentioning
confidence: 95%
“…TLR2 and TLR4 are able to trigger signal transduction by recruiting MyD88, which drives activation of the transcription factor nuclear factor-κB, leasing to the expression of proinflammatory cytokines. It has been demonstrated that TLR2 and TLR4 may interact with MTB, and that they are associated with the immune response to MTB infection (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Since M. bovis BCG has been reported to induce M1 macrophages [6] and, in contrast, M2-polarized macrophages have been reported to contribute to tissue remodeling [7], we employed immunohistochemical staining for CD68 (fig. 2a), iNOS (fig.…”
Section: Case Reportmentioning
confidence: 99%